2011
DOI: 10.1093/schbul/sbr183
|View full text |Cite
|
Sign up to set email alerts
|

P50 Suppression and Its Neural Generators in Antipsychotic-Naïve First-Episode Schizophrenia Before and After 6 Months of Quetiapine Treatment

Abstract: The present findings suggest that P50 suppression deficits are already present at an early stage of schizophrenia. Furthermore, particularly those patients with more severe gating deficits appeared to need higher dosages of quetiapine, although their clinical symptoms did not seem to indicate this. Quetiapine treatment significantly improved these gating deficits. Furthermore, a frontocentral source in the brain appeared to be involved in the deficient P50 gating of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…Similarities such as increased baseline gamma power, decreased evoked gamma power, decreased P1 suppression and decreased PPI (Braff et al, 1992; Freedman et al, 1996, 1983; Hanlon et al, 2005; Kwon et al, 1999; Spencer et al, 2003), as well as decreased MMN amplitude in both disorders (Atkinson et al, 2012; Baldeweg et al, 2002) have been reported in both ASD and schizophrenia. However, other studies indicate that there might be marked differences, such as that some studies found normal levels of both PPI and P1 suppression in children with autism (Kemner et al, 2002; Kemner et al, 1995; Kohl et al, 2014; Madsen et al, 2015; Oranje et al, 2013b; Ornitz et al, 1993), while deficient levels are robustly found in schizophrenia (Aggernaes et al, 2010; Braff et al, 2001; Oranje et al, 2013a; Thibaut et al, 2015). There seems to be at least some overlap between schizophrenia and autism symptoms: in two Danish register based studies it was shown that, dependent on the specific form of autism, up to 30% of individuals with a childhood diagnose of autism develop a schizophrenia spectrum disorder later in life (Mouridsen et al, 2008a,b), while parental reports suggest that up to 60% of patients with schizophrenia have had a history with autistic symptoms (Unenge Hallerback et al, 2012).…”
Section: Overlapping Sensory Processing Deficits In Asd and Schizomentioning
confidence: 99%
“…Similarities such as increased baseline gamma power, decreased evoked gamma power, decreased P1 suppression and decreased PPI (Braff et al, 1992; Freedman et al, 1996, 1983; Hanlon et al, 2005; Kwon et al, 1999; Spencer et al, 2003), as well as decreased MMN amplitude in both disorders (Atkinson et al, 2012; Baldeweg et al, 2002) have been reported in both ASD and schizophrenia. However, other studies indicate that there might be marked differences, such as that some studies found normal levels of both PPI and P1 suppression in children with autism (Kemner et al, 2002; Kemner et al, 1995; Kohl et al, 2014; Madsen et al, 2015; Oranje et al, 2013b; Ornitz et al, 1993), while deficient levels are robustly found in schizophrenia (Aggernaes et al, 2010; Braff et al, 2001; Oranje et al, 2013a; Thibaut et al, 2015). There seems to be at least some overlap between schizophrenia and autism symptoms: in two Danish register based studies it was shown that, dependent on the specific form of autism, up to 30% of individuals with a childhood diagnose of autism develop a schizophrenia spectrum disorder later in life (Mouridsen et al, 2008a,b), while parental reports suggest that up to 60% of patients with schizophrenia have had a history with autistic symptoms (Unenge Hallerback et al, 2012).…”
Section: Overlapping Sensory Processing Deficits In Asd and Schizomentioning
confidence: 99%
“…Effects of haloperidol and reboxetine on sensory gating L Witten et al antipsychotic naive, first-episode patients with schizophrenia (eg, Oranje et al, 2013), our current data raise the possibility that D2 antagonism may contribute to the P50 suppression deficits reported from studies on medicated patients with schizophrenia. Similar to our human P50 gating data, haloperidol disrupted gating (N1) in the hippocampus of rats.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, it has been shown that haloperidol significantly reduces baseline levels of NE in rats (Amato et al, 2011). A growing body of evidence has indicated that an optimal functional PFC is essential for normal levels of gating (Bak et al, 2011;Oranje et al, 2006Oranje et al, , 2013Weisser et al, 2001). Interestingly, there is no dopamine transporter in the rat PFC, nor in humans as a matter of fact: dopamine in the PFC is removed by NET (Carboni et al, 1990;Pozzi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations